The influence of the Completeness of Islamic Religious Education Learning Facilities on Student Learning Outcomes at UPT. SD Negeri 16 Sido Mulyo Medang Deras District Coal District - Julyanti , Nurmalena; Parinduri, Sari Atika; Pratiwi, Indah Dina (At-Tarbiyah: Journal of Islamic Religious Research and Education, 2023)
This research approach is a quantitative approach, namely research where the data obtained is related to numbers which causes the use of statistical analysis techniques. The results of the research in this thesis, based on calculations, the coefficient of determination is 18.31%. Thus it can be seen that the value of the contribution of the completeness of learning facilities in the subject of Islamic Religious Education to the learning outcomes of UPT students. SD Negeri 16 Sido Mulyo, Medang Deras District, Batu Bara Regency by 18.31% and the remaining 82% (100% -18%) is influenced by variables that were not examined in this study such as learning motivation, learning environment, methods and learning strategies and so on. The results of the analysis show that in the product moment value table "r" df 76, then with a df of 74 the rtable value is obtained at a significant level of 5% of 0.227, while at a significant level of 10% the rtable value is 0.227. It turns out that rxy (magnitude = 0.428) is much larger than rtable (which is 0.227 and 0.296). Because rxy is greater than rtable, thus the alternative hypothesis (Ha) is accepted and the null hypothesis (Ho) is rejected, because there is a significant positive relationship between the completeness of learning facilities in Islamic religious education subjects and UPT student learning outcomes. SD Negeri 16 Sido Mulyo, Medang Deras District, Batu Bara Regency